OPTIMIZATION BUILDING PERFORMANCE IN EARLY DESIGN STAGE USING INTEGRATED DYNAMIC MODEL - Sari, Dany Perwita; Laksana, Pradhana Jati Budhi (MODUL, 2020)
Considering the magnitude of energy loss in building, development of energy saving methods appears to be essential. Daylight plays a significant role in designing energy efficient buildings and improving visual comfort for the occupants. Many daylight analysis methods have been developed in this area. Most of these methods focus on opening maximization. These methods unfortunately might reduce comfort since it causes direct solar glare. There is a need for a reliable lighting simulation model to control the lighting strategy in early stage design. This study proposes a strategy for visualizing daylight analysis of buildings by using Integrated Dynamic Model (IDM). IDM is a combination of design tools used during the conceptual phase for holistic classroom that considers the building’s energy usage, daylight distribution, and thermal indoor environment. The optimization focus is related maximize the performance of the building envelope design. The purpose of this paper are; firstly, providing a new strategy for visualizing the predicting daylight while respecting architectural integrity. The second purpose is to facilitate the designer for choosing window and envelope design alternatives during early stages. The third is to maximize the positive impacts of daylight. Lastly, hopefully IDM could present a simplified simulation and analyze method with the timely, accurate and efficient process.